Pengaruh Current Ratio, Debt To Equity Ratio, Total Assets Turn Over, Return On Assets, Earning Per Share Dan Price Earning Ratio Terhadap Pertumbuhan Laba - Silvia Indrarini; Audrey Mike Wijaya (Akubis : Jurnal Akuntansi dan Bisnis, 2021)
The purpose of this study was to examine the effect of Current Ratio, Debt to Equity Ratio, Total Assets Turn Over, Return On Assets, Earning Per Share and Price Earning Ratio on Profit Growth of Manufacturing Companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This type of research is explanatory research with a population of 197 companies and the sampling technique using purposive sampling technique produces 56 company samples. The results of the analysis show that the Current Ratio, Debt to Equity Ratio, Total Assets Turn Over, Return On Assets, Earning Per Share and Price Earning Ratio simultaneously affect profit growth. Current Ratio, Return On Assets and Price Earning Ratio partially affect profit growth. Return On Assets (ROA) has the most dominant effect on profit growth in manufacturing companies.